2005
DOI: 10.1038/sj.onc.1208589
|View full text |Cite
|
Sign up to set email alerts
|

Partial downregulation of MAD1 causes spindle checkpoint inactivation and aneuploidy, but does not confer resistance towards taxol

Abstract: The mitotic spindle assembly checkpoint ensures proper chromosome segregation during mitosis by inhibiting the onset of anaphase until all kinetochores are attached to the mitotic spindle and tension across the kinetochores is generated. Here, we report that the stable partial downregulation of the spindle checkpoint gene MAD1, which is observed in human cancer, leads to a functional inactivation of the spindle checkpoint resulting in gross aneuploidy. Interestingly, although Mad1 is thought to act as a kineto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
1
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 59 publications
8
72
1
3
Order By: Relevance
“…The active SAC when HDAC functions are disrupted [95][96][97]. In line with these findings, HDACIs (TSA, apicidin and sodium butyrate) induce premature sister chromatid separation [95], a phenotype consistently observed when the SAC is inhibited by RNA interference or genetic means [98][99][100]. Securin proteasome-dependent degradation is also observed in TSA treated mitotic cells and most likely accounts for premature sister chromatid separation [95].…”
Section: The Spindle Assembly Checkpointsupporting
confidence: 64%
“…The active SAC when HDAC functions are disrupted [95][96][97]. In line with these findings, HDACIs (TSA, apicidin and sodium butyrate) induce premature sister chromatid separation [95], a phenotype consistently observed when the SAC is inhibited by RNA interference or genetic means [98][99][100]. Securin proteasome-dependent degradation is also observed in TSA treated mitotic cells and most likely accounts for premature sister chromatid separation [95].…”
Section: The Spindle Assembly Checkpointsupporting
confidence: 64%
“…Controversial results have been reported on the effect of mitotic checkpoint inhibition on taxol-induced cell death. Incomplete functioning of the checkpoint has been suggested to induce resistance to high doses of taxol (17)(18)(19)(20), which is in line with the observation that CIN also correlated with taxol resistance (21). However, others have shown that inhibition of the mitotic checkpoint increases the effectiveness of taxol (22).…”
supporting
confidence: 68%
“…13,25,27,29 Suppression of Mad2 or BubR1 in paclitaxeltreated breast cancer MCF-7 cells has been shown to abolish spindle checkpoint function, resulting in enhanced paclitaxel resistance. 29 The findings presented here strongly suggest that BRCA1 deficiency mediates paclitaxel resistance, at least in part, through downregulation of BubR1 expression resulting in premature inactivation of spindle checkpoint in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Surprisingly, spindle checkpoint deficiency has recently been associated with resistance to anti-microtubule agents. [25][26][27][28][29] Direct evidence that the induction of dysfunctional spindle checkpoint results in paclitaxel resistance has been demonstrated by knocking down Mad2 and/or BubR1 in MCF-7 breast carcinoma cells. 29 These cells harbor functional p53 but lack caspase-3 30 and undergo cell death following paclitaxel treatment by showing very weak apoptotic response but high micronuclei formation.…”
Section: Introductionmentioning
confidence: 99%